Geomorphological sedimentary characteristics in the coastal area of Ma river delta, Thanh Hoa province - Nguyen, Minh Quang; Vu, Van Ha; Mai, Thanh Tan; To, Xuan Ban; Tran, Ngoc Dien; Dang, Minh Tuan; Dang , Xuan Tung; Nguyen, Thi Min; Hoang, Van Tha; Giap , Thi Kim Chi (Vietnam Journal of Marine Science and Technology, 2021)
The coastal area of the Ma river delta is formed by the interaction of continental and marine processes, between neo-tectonic activities and exogenous processes, between natural factors and human activities during the Late Holocene. Using remote sensing and geoscience research methods (granulometry, paleontology, geochemistry, clay mineralogy) and geomorphological studies (geneses, morphology, dynamics) combined with field survey, this coastal area, except the denuded mountainous remnants, could be distinguished into 12 morpho-sedimentary units formed and developed by the dynamic interactions of the river, waves and tides. The units formed by fluvial dynamics include: 1) Point bar is composed of clayey silt and sandy silt, 2) Channel bar composed of silty sand, 3) Levee with the composition of silty sand and 4) The flood plain of silty clay. The Late Holocene evolution of the Ma river delta was dominated by wave dynamics, reflected by a wave-formed association of dunes, interdune swamps and current sand beaches. The wave-formed units include 5) Dune’s sand and silty sand, 6) Back-dune depressions composed of sand silt clay, 7) Beach composed of sand, 8) Lagoon plain of silty clay and 9) Strand plain composed of silty sand. The tide-influenced units include 10) Supratidal flat with the composition of silty clay, 11) Intertidal flat characterized by clay or silty clay interbedded with thin fine sand or silty sand layers, 12) Subtidal flat of sand and silty sand.